Micronized purified flavonoid fraction (daflon) improves sexual function by modulating NF-kB /NO/cGMP and steroidogenic signaling in cisplatin-treated male Wistar rats - Akhigbe RE; Akhigbe TM; Adegbola CA (Biochemistry and Biophysics Reports)
Cisplatin is known to induce sexual dysfunction by suppressing testosterone levels. It also upregulates nuclear factor-kappa B (NF-kB), which mediates nitric oxide (NO)-dependent endothelial dysfunction. This study evaluated the effects of daflon, a micronized purified flavonoid fraction that contains diosmin and hesperidin, on the NF-kB/NO/cyclic guanosine monophosphate (cGMP) and steroidogenic signaling pathways in cisplatin-induced male sexual dysfunction. Thirty-two male Albino Wistar rats were randomly assigned to four groups: vehicle-treated, daflon-treated, cisplatin-treated, and cisplatin plus daflon-treated. Cisplatin administration resulted in impaired sexual function, characterized by prolonged latencies for mounting, intromission, and ejaculation, as well as a decrease in mating motivation and the frequencies of these behaviors. Additionally, cisplatin reduced sperm quality and downregulated NO/cGMP levels through the upregulation of NF-kB and MDA and downregulation of GSH, which is critical for maintaining endothelial function. Furthermore, cisplatin suppressed serum levels of luteinizing hormone (LH) and follicle-stimulating hormone (FSH) and inhibited the activities of testicular 3β-hydroxysteroid dehydrogenase (3β-HSD) and 17β-hydroxysteroid dehydrogenase (17β-HSD), leading to decreased serum testosterone and dopamine levels. Co-administration of daflon with cisplatin resulted in the downregulation of NF-kB and MDA and an increase in GSH, NO, and cGMP production. Daflon co-treatment also upregulated LH, FSH, 3β-HSD, and 17β-HSD, as well as circulating testosterone and dopamine levels, which corresponded with improved sexual function, evident from enhanced mating motivation and improved latencies and frequencies of mounting, intromission, and ejaculation. In conclusion, the daflon improved sexual function in rats treated with cisplatin. This involved the downregulation of NF-kB and enhancement of the cavernosal NO/cGMP pathway and testicular steroidogenic signaling.